Climate change, out-migration and agrarian stress: the potential for upscaling small-scale water storage in Nepal - Bharati, Luna; Gurung, Pabitra; Maharjan, L.; Janmaat, J.; Price, J.I.; Sherpa, Tashi Yang Chung; Bhattarai, Utsav; Koirala, S.; Timilsina, B. (International Water Management Institute, 2014)
Climate change could have a critical impact on agriculture in Nepal due to dry-season water shortages, and changes in the variability of water availability and associated uncertainty. This makes water storage systems (most notably ponds and tanks) increasingly important. This report explores the potential role of small-scale water storage infrastructure in two subbasins within the larger Koshi River Basin in central and eastern Nepal, yet shows that upscaling such infrastructure requires an appreciation of the other drivers of change in agriculture aside from climate (e.g., rising cost of living and poor terms of trade for agriculture). It also identifies the social relations and dynamics (distribution of land, water and labor) which could mediate the success of future interventions. It is clear from the research that, while small-scale water storage has the potential to significantly strengthen livelihoods in the Nepali hills, it is necessary to tailor projects to the existing political-economic context.